Biocatalytic Insights for The Synthesis of New Potential Prodrugs: Design of two Ibuprofen Derivatives - Zappaterra, F; Presini, F; Venturi, V; Lerin, LA; Giovannini, PP; Costa, S (Applied Sciences, 2023)
Due to its effectiveness, ibuprofen is one of the most popular anti-inflammatory drugs worldwide. However, the poor water solubility of this active ingredient severely limits its spectrum of pharmaceutical formulations (and often results in severe adverse effects due to high administered doses). To overcome these limitations, in this work, we enzymatically synthesized more hydrophilic derivatives of ibuprofen through its covalent attachment to two biobased polyalcohols: erythritol and glycerol. Herein, we report the optimized reaction conditions to produce an IBU-erythritol ester (82% & PLUSMN; 4% of conversion) by using Candida antarctica lipase B (CalB). Furthermore, we also report the enantioselective solventless esterification of (S)-ibuprofen with glycerol (83% & PLUSMN; 5% of conversion), exploiting immobilized Rhizomucor miehei lipase as a biocatalyst. The full NMR characterizations of the prodrug esters were performed via 1H, 13C-NMR, DEPT, COSY, HSQC, and HMBC-NMR. The approach reported in this work can be extended to a large variety of poorly water-soluble active pharmaceutical ingredients (APIs).